EPIDEMICS OF SEVERE ACUTE RESPIRATORY SYNDROME (SARS) IN THE WORLD (REVIEW) - G. G. Onishchenko; A. S. Maramovich; S. A. Kosilko; S. P. Merinov (Acta Biomedica Scientifica, 2020)
Study materials of a new disease epidemic, symbolically named as a severe acute respiratory syndrome (SARS), emerged in the late 2002 at south China are reviewed. The significance of the first patients as the major sources of the infection around which plural foci were formed is shown. Infections happened in hotels, hospitals, multistory dwelling houses and in places of mass crowds. Medical workers are attributed to a group of high infection risk. The role of high-speed transport means in the disease dissemination to short and long distances is established. This infection was imported to 32 countries on five continents, but the secondary epidemic complications occurred only in Hong Kong, Singapore, Taiwan, Vietnam and Canada. Global SARS dissemination requires international collaboration and coordination of this infection surveillance system.